THE EFFECT OF COMPANY SIZE, PROFITABILITY, AND LIQUIDITY ON COMPANY VALUE IN BANKING SUBSECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (PERIOD 2020-2023) - Dewi, Ni Luh Ketut Charisma Cahya; Gunadi, I Gusti Ngurah Bagus; Permadi, I Komang Oka (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
The concept of company value emerges as a pivotal factor that investors must consider prior to making investment decisions concerning a particular company. The average company value or Price Book Value (PBV) has been observed to undergo a persistent decline from 2020 to 2023. The objective of this study is to ascertain the impact of company size, profitability, and liquidity on company value in banking sub-sector companies listed on the IDX. The population for this study comprised all banking companies listed on the IDX from 2020 to 2023, a total of 47 entities. The purposive sampling method was employed to ascertain the sample size, which resulted in a total of 30 companies and 120 observations over a period of four years. Multiple linear regression analysis was employed to examine the research data. The findings of this study indicated that the size of the company does not exert any influence on the value of banking sub-sector companies that are listed on the IDX. The findings of this study demonstrate that profitability exerts a positive and significant effect on the value of banking sub-sector companies listed on the IDX. The findings of this study demonstrate that liquidity exerts a positive and significant effect on the value of banking sub-sector companies listed on the IDX.